2016
DOI: 10.1590/1983-084x/15_021
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros de qualidade físico-químicos e avaliação da atividade antioxidante de folhas de Plectranthus barbatus Andr. (Lamiaceae) submetidas a diferentes processos de secagem

Abstract: Quality of the leaves of Plectranthus barbatus Andr. (Lamiaceae) dried in solar dryer and oven. This paper describes the physicochemical composition, the evaluation of the antioxidant activity by free DPPH radicals using the scavenging method, the determination of flavonoids and total phenolic compounds of ethanol, acetone and aqueous extracts of the medicinal plant Plectranthus barbatus Andr. (Lamiaceae), dehydrated in solar dryer and circulation oven at 60 °C. Water activity rates for two drying methods were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
3
0
2
Order By: Relevance
“…5O e 5P) no parênquima da nervura central, no parênquima do mesofilo, no colênquima angular do pecíolo e no parênquima medular do caule. As três espécies em estudo apresentam compostos antioxidantes, dentre os quais se destacam os compostos fenólicos, que também é encontrado em outra espécie da família Lamiaceae como Origanum vulgare L. (GONÇALVES et al, 2015) e Plectranthus barbatus (SILVA et al, 2016). Os compostos fenólicos se destacam por suas propriedades antioxidantes, anti-inflamatórias, protetora de órgãos vitais, incluindo o sistema cardiovascular (HITZ et al, 2018).…”
Section: Resultsunclassified
“…5O e 5P) no parênquima da nervura central, no parênquima do mesofilo, no colênquima angular do pecíolo e no parênquima medular do caule. As três espécies em estudo apresentam compostos antioxidantes, dentre os quais se destacam os compostos fenólicos, que também é encontrado em outra espécie da família Lamiaceae como Origanum vulgare L. (GONÇALVES et al, 2015) e Plectranthus barbatus (SILVA et al, 2016). Os compostos fenólicos se destacam por suas propriedades antioxidantes, anti-inflamatórias, protetora de órgãos vitais, incluindo o sistema cardiovascular (HITZ et al, 2018).…”
Section: Resultsunclassified
“…P. barbatus main constituents isolated from different parts of this species are diterpenoids, and these phytochemicals are responsible for many described biological activities (Alasbahi and Melzig, 2010). However, the presence of phenolic compounds in P. barbatus extracts has been reported in several studies (Brito et al, 2018, Ganash & Qanash, 2018, Shaheen et al, 2017, Silva et al, 2016, Rodrigues et al, 2016. Thus, in order to elucidate the biological activities of P. barbatus leaves extracts that contains phenolic compounds, here we conducted the evaluation of ConA (stimulated control) [128.63 pg.mL -1 (55.79 pg.mL -1 -387.76 pg.mL -1 )].…”
Section: Discussionmentioning
confidence: 99%
“…However, this compound has a water-insoluble nature that limits its clinical utility (Alasbahi and Melzig, 2010). Other phytochemicals such as the phenolic derivatives nepetoidins A and B (Grayer et al, 2003) and rosmarinic acid (Falé et al, 2011) were also found in P. barbatus composition (Silva et al, 2016). Phenolic plant-derived compounds comprise the composition of several classes of molecules such as simple phenolics, phenolic acids, coumarins, flavonoids, hydrolysable and condensed tannins, stilbenes, lignans and lignins (Silva et al, 2019) and, some of these have already been identified in P. barbatus extracts (Borges et al, 2020;Ezeonwumelu et al, 2019;Rodrigues et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados com produtos naturais têm demonstrado a influência da temperatura de secagem e do solvente extrator na atividade antioxidante e na extração de compostos bioativos [23][24][25][26] .…”
Section: Introductionunclassified